Soil geochemistry of the municipality necropolis of Mata, RS, by fluorescence of x-rays by dispersive energy - Gomes, Cristiane Heredia; Sperandio, Diogo Gabriel; Dias, Guilherme Pazinato; Viçozzi, Arthur Pedroso (Ciência e Natura, 2020)
The objective of this study was to detect the environmental impacts generated by the municipal Mata cemetery. In order to aid in the detection and monitoring of the area were used granulometric and chemical terms through EDXRF the study of soil. Considering the results obtained it is concluded that the soil analytical results showed presence of metals in all analyzes, but with levels below the maximum permitted values of metals in Brazilian soils. The Cd was an exception, for this metal values above 0.6 mg kg-1 were found. The clay/silt ratio less than 1.5 in the investigated samples indicates a more weathered soil on the surface than at depths of 30 cm in the cemetery area. Statistical data estimate highly significant Mg, Cl, Al, Fe, K, Ti and Rh factor loads on the surface and at depths, K, Ca, Cl, Al and Mg are the most important. The main ion exchanges correlate with the correlation coefficients found within the same order. Therefore, it is possible that the simultaneous increase or decrease in the cations is the result, mainly, of ionic exchange effects in the mineral assembly of the sediments investigated.